Kajian Landing Station Alat Deteksi Dini Tsunami Berbasis Kabel Serat Optik Bawah Laut di Kabupaten Pasangkayu, Sulawesi Barat - Puspa Khaerani; Heru Sri Naryanto; Dian Nuraini Melati; Syakira Trisnafiah (Agency for the Assessment and Application of Technology / Badan Pengkajian dan Penerapan Teknologi (BPPT), 2021)
The construction of an underwater fiber-optic cable-based tsunami early detection system is planned to be installed in the Makassar Strait with a landing point in West Sulawesi. Land infrastructure such as a Power House (PH), a communication tower, and a Beach Manhole (BMH) is needed to sustain the system's power in order to survive. Therefore, the aim of this scientific paper is to study several alternative landing station locations in Pasangkayu, West Sulawesi and then determine the priority locations. The methods used to achieve these objectives are field observation methods and secondary data analysis based on parameters of land area conditions, environmental conditions, supporting infrastructure, social conditions and licensing systems, and marine activities. These aspects are then assessed to determine the priority of the selected location. The location selected based on the assessment carried out is ALT-02B. In succession, the three priority locations selected from the order of most priority to least priority are ALT-02B, ALT-02A, and ALT-06. This selected priority location is not necessarily the final choice location to be used in the construction of a tsunami early detection system land infrastructure because in the process there are still things to be considered and aspects that are made the main priority for consideration in making decisions.